Seasonal diet changes in elephant and impala in mopane woodland - Kos, Martine; Hoetmer, Arno J; Pretorius, Yolanda; de Boer, Willem Frederik; de Knegt, Henjo; Grant, C. C; Kohi, Edward; Page, Bruce; Peel, Mike; Slotow, Rob; van der Waal, Cornelis; van Wieren, Sipke E; et al. (European journal of wildlife research, 2012)
Elephant and impala as intermediate feeders, having a mixed diet of grass and browse, respond to seasonal fluctuations of forage quality by changing their diet composition. We tested the hypotheses that (1) the decrease in forage quality is accompanied by a change in diet from more monocots in the wet season to more dicots in the dry season and that that change is more pronounced and faster in impala than in elephant; (2) mopane (Colophospermum mopane), the most abundant dicot species, is the most important species in the elephant diet in mopane woodland, whereas impala feed relatively less on mopane due to the high condensed tannin concentration; and (3) impala on nutrient-rich soils have a diet consisting of more grass and change later to diet of more browse than impala on nutrient-poor soils. The phosphorus content and in vitro digestibility of monocots decreased and the NDF content increased significantly towards the end of the wet season, whereas in dicots no significant trend could be detected. We argue that this decreasing monocot quality caused elephant and impala to consume more dicots in the dry season. Elephant changed their diet gradually over a 16-week period from 70% to 25% monocots, whereas impala changed diets rapidly (2–4 weeks) from 95% to 70% monocots. For both elephants and impala, there was a positive correlation between percentage of monocots and dicots in the diet and the in vitro digestibility of these forage items. Mopane was the most important dicot species in the elephant diet and its contribution to the diet increased significantly in the dry season, whereas impala selected other dicot species. On nutrient-rich gabbroic soils, impala ate significantly more monocots than impala from nutrient-poor granitic soils, which was related to the higher in vitro digestibility of the monocots on gabbroic soil. Digestibility of food items appears to be an important determinant of diet change from the wet to the dry season in impala and elephants.